New estimates of single photon parameters for satellite-based QKD - Ali, Sellami; Wahiddin, Mohamed Ridza (Elsevier, 2009)
A new decoy state method has been presented to tighten the lower bound of the key generation rate for BB84 using one decoy state and one signal state. It can give us different lower and upper bounds of the fraction of single-photon counts and single-photon QBER, respectively, for one decoy state protocol. We have also analyzed the feasibility of performing quantum key distribution (QKD), with different exiting protocols, in earth-satellite and intersatellite links. Our simulation shows the choice of intensity of signal state and the effect of choosing the number of decoy states on key generation rate. The final key rate over transmission distance has been simulated, which shows that security proofs give a zero key generation rate at long distances (larger than 16,000 km). It has been shown that the practical QKD can be established with low earth orbit and medium earth orbit satellites.